CATATAN PERILAKU HIDUP BERSAMA TANAMAN SUKU ANNONCEAE DENGAN SEMUT DI KEBUN RAYA BOGOR - Tri Handayani (Gunung Djati Conference Series, 2023)
The relationship between plants and ants occurs in various plant's life phases. Some species of plants provide both food and nesting space for the ants that protect them against herbivores. The Annonaceae plants are known as a habitat for ants. However, the information about their relationship is still lacking. The research reported in this paper to observe and record ants species on fiveteen Annonaceae plants selected and their relationship in Bogor Botanic Gardens. Direct observation at the Bogor Botanic Gardens and literatur study were used as methods in this study. The results showed that the most common ants that live in the Annonaceae plants selected, namely Camponotus sp, Dolichoderus thoracicus, Polyrhachis sp, and Oecophylla smaragdina. The ants are found in plant parts, viz. root, branch, stem, leaf, flower and fruit. The plants gain protection against herbivores, while ants get food and nesting place from this relationship. Indirectly, ants also enrich the soil around the plant. On the other hand, ants are predicted to reduce the success of plant pollination.